Tatar educators in the system of public education of Turkestan - Yulchibayev , Jahongir Shakirovich (The Lingua Spectrum, 2026)
This article analyzes the participation of representatives of the Tatar intelligentsia in the formation and development of the public education system in the Fergana region during the 1920s, based on archival documents. Particular attention is paid to the role of Tatar teachers and administrative staff in educational institutions of the region, as well as to the activities of Tatar-Bashkir schools. The study examines issues related to the personnel policy of public education authorities, the training of pedagogical staff, the development of vocational education, and the implementation of educational reforms. The use of archival materials makes it possible to identify the significant contribution of Tatar specialists to the modernization of the regional education system and to the spread of enlightenment in Central Asia.